Performance Analysis of Threshold Based Algorithms under Wormhole Attack in MANET - Kalpana, G; Archana, S (International Journal of Computer Sciences and Engineering, 2025)
An ad hoc network refers to a network connection established for a single session and does not essential a router or a wireless base station. A MANET is a collection of mobile nodes connected through wireless networks. MANET can join and leave the network dynamically. However, MANET is particularly vulnerable due to its fundamental characteristics, such as dynamic topology, distributed co-operation, and constrained capability. One main challenge on designing these networks is their vulnerability to security attacks.In this paper the performance of Threshold Based Algorithms using routing protocols AODV and DSR with wormhole attack detection have been analysed using NS2 considering various parameters such as packet delivery ratio and average throughput to evaluate its performance.